Effect of exposure of cotton dust on pulmonary function tests in female workers of spinning mill at Malegaon, Maharashtra - Anita J. Jadhav; Shital R. Mankar; Chadrashekhar D. Dange (International Journal of Medical Research and Review, 2016)
Background: Textile industry is the only industry to have employed women workers since long time. There are many respiratory problems develop in the women workers.Aims and Objective: The aim of this study was to assess the effects of exposure of cotton dust on the pulmonary function in the spinning mill female workers.Method: We enrolled 35 female (age=18 to 50 years) workers in study group who were regularly working in spinning mill and duration of exposure to cotton dust was noted. Inclusion criteria were clinically healthy, non-smokers, without chronic respiratory disease, systemic illness. Tobacco users were excluded. Control group consist 35 female (age=18 to 50 years) who were never in exposure of cotton wool. This study was conducted after obtaining ethical clearance and consent. MEDSPIROR-COMPUTERISED SPIROMETER was used to find out pulmonary function tests which were FVC, FEV1, FEV1/FVC and PEFR, which helped in evaluating pulmonary functions.Statistical Analysis: Unpaired students ‘t’ test was applied to compare the PFT parameters in study group and control group . The data was expressed as mean + standard deviation.Results: Greater declines were seen in forced vital capacity, forced expiratory volume in first second. This reduction was significant in FEV1/FVC which is indicator of early obstructive pattern in the exposed group. As duration of exposure increases FVC reduces and showed restrictive pattern.Conclusion: According to our study, cotton textile workers developed respiratory problems which reflects as reduces pulmonary function.